Statistical Mechanics for Engineers - Kusaka, Isamu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book provides a gentle introduction to equilibrium statistical mechanics. The particular aim is to fill the needs of readers who wish to learn the subject without a solid background in classical and quantum mechanics. The approach is unique in that classical mechanical formulation takes center stage. The book will be of particular interest to advanced undergraduate and graduate students in engineering departments.
Classical Mechanics -- Thermodynamics -- Classical Statistical Mechanics -- Various Statistical Ensembles -- Simple Models of Adsorption -- Thermodynamics of Interface -- Statistical Mechanics of Inhomogeneous Fluids -- Quantum Formulation -- Vectors in 3-Dimensional Space -- Useful Formulae -- Legendre Transformation -- Dirac Function -- Where to Go from Here -- List of Greek Letters -- Hints to Selected Exercises -- Index.
Keywords: Chemical engineering; Chemistry, Physical and theoretical; Statistical physics; Dynamical systems; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Industrial Chemistry/Chemical Engineering; Theoretical and Computational Chemistry; Complex Systems; Engineering Thermodynamics, Heat and Mass Transfer; Statistical Physics and Dynamical Systems